Assessing the factors driving the changes in the spatio-temporal distribution of Hepatus pudibundus (Decapoda, Brachyura) over a 20-year interval in a region under the influence of El Niño (ENSO) - Teles, Jeniffer Natalia [UNESP]; Mantelatto, Fernando Luis; Castilho, Antonio Leão [UNESP]; Fransozo, Adilson [UNESP]; Bertini, Giovana [UNESP] (Wiley, 2020)
This study aimed to compare the spatio-temporal distribution of demographic groups of Hepatus pudibundus in the Ubatuba Bay, São Paulo, Brazil, over a 20-year interval. Two 1-year samplings were conducted: the 1st period (P1) ran from September 1995 to August 1996 and the 2nd period (P2) ran from September 2016 to August 2017. Samples were taken from five stations that differed in depth (5, 10, and 15 m) and location (exposed area and sheltered area), aboard a shrimp fishing boat. Over the 20-year period, the percentage of fine sediment increased in all stations. In total, we captured 865 H. pudibundus individuals in the P1 and 4,222 in the P2. The higher abundance seen in the P2 may have been caused by the effects of an intense ENSO event in Ubatuba, as well as co-occurring protective actions against fisheries activities in the region. The spatial distribution also changed after 20 years: In the P1, H. pudibundus were more concentrated in the 15 m station and exposed area, but they shifted to the sheltered area in the P2. This change may be related to the increase of fine sediments in this area, and to the fact that it is naturally protected from fisheries. According to the correspondence analysis, the abundance of males and juveniles was correlated with spring and winter, respectively. In the P1, females were more abundant in spring, whereas in the P2 they were more abundant in summer, which may be explained by a higher nutrient availability to the larvae in the summer of the P2. Our comparisons over the 20-year interval revealed that the spatio-temporal distribution of H. pudibundus has changed and that the population is well established in Ubatuba Bay.
Keywords: Aethroidea; bycatch; crab; marine protected area (MPA); sedimentation process; temporal scale